Literacy activities in teacher learning planning for Indonesian language subjects in middle schools - Adi, Pidekso; Suyitno, Imam; Harsiati, Titik; Basuki, Imam Agus (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
Strengthening literacy competency is an effort to improve the quality of students in facing future challenges. The rapid flow of information has consequences for humans to be able to choose and sort information that is useful or beneficial for improving their welfare. For this reason, literacy competency is an important skill to be part of learning activities in educational institutions. Educational institutions are strategic institutions for strengthening literacy competency. In this regard, good and effective planning prepared by teachers must ensure that it contains activities that support the learning process that strengthen literacy competency. For this reason, this study examines literacy activities in the planning of Indonesian Language Subjects with a qualitative approach. Data were obtained from documents in the form of RPP and teaching modules from teachers who had been trained in literacy by the Directorate of Junior High Schools, Ministry of Education, Culture, Research and Technology. The results show that the activities in these steps show a variety of activities that are interpreted as literacy competency strengthening activities. Potential strategies that emerge from learning steps vary because they are influenced by learning objectives and topics. Disposition can be accommodated in the sense that the formation of students’ behavioral dispositions is potentially easily formed. This depends on the implementation of continuous strategies in every learning process.